2020
DOI: 10.1017/pab.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Live, dead, and fossil mollusks in Florida freshwater springs and spring-fed rivers: Taphonomic pathways and the formation of multisourced, time-averaged death assemblages

Abstract: Taphonomic processes are informative about the magnitude and timing of paleoecological changes but remain poorly understood with respect to freshwater invertebrates in spring-fed rivers and streams. We compared taphonomic alteration among freshwater gastropods in live, dead (surficial shell accumulations), and fossil (late Pleistocene–early Holocene in situ sediments) assemblages from two Florida spring-fed systems, the Wakulla and Silver/Ocklawaha Rivers. We assessed taphonomy of two gastropod species: the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…Death assemblages, the loose collection of shell material that accumulates in scours, divots, or similar erosional depressions on the river bottom, are also commonly used in conservation paleobiological research (e.g., Brown et al, 2005). While molluscan death assemblages were collected for this study, their complicated, multi-sourced provenance (Kusnerik et al, 2020) led to their exclusion from further analyses.…”
Section: Study Area and Field Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Death assemblages, the loose collection of shell material that accumulates in scours, divots, or similar erosional depressions on the river bottom, are also commonly used in conservation paleobiological research (e.g., Brown et al, 2005). While molluscan death assemblages were collected for this study, their complicated, multi-sourced provenance (Kusnerik et al, 2020) led to their exclusion from further analyses.…”
Section: Study Area and Field Methodsmentioning
confidence: 99%
“…Almost all fossil species present are shared between the two systems, with those absent from the Wakulla relatively rare in Silver/Ocklawaha samples. Given that radiocarbon dates on mollusk fossils coincide with the activation of spring flow across much of Florida (Balsillie and Donoghue, 2011;Donoghue, 2011;O'Donoughue, 2015;Kusnerik et al, 2020), the observed faunal resemblance of the two relatively distant river systems suggests that Florida springs and rivers were initially colonized by a similar suite of mollusks, reflected in the similarity of their fossil assemblages. Many fossil species identified in this survey have also been documented in freshwater fossil assemblages elsewhere in Florida (Karrow et al, 1996;Auffenberg et al, 2006), further suggesting that similar mollusk assemblages populated multiple Florida springs and rivers during the late Pleistocene-early Holocene.…”
Section: Fossil Community Compositionmentioning
confidence: 99%
See 3 more Smart Citations